2020
DOI: 10.18203/2320-1770.ijrcog20200353
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of simple International ovarian tumor analysis ultra sound rules in differentiating between benign and malignant ovarian tumors and their histopathological correlation

Abstract: Background: IOTA (International ovarian tumor analysis) study is considered one of the largest studies on ultrasound diagnosis of ovarian pathology conducted in literature till date. It was started in 1999 and included nine European countries. It is a standardized technique for preoperative classification of ovarian pathology defined by IOTA group.Methods: A retrospective study was analyzed from a period of January 2016 to December 2017 (2-year period). The records of all the patients operated for benign and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
1
1
0
Order By: Relevance
“…In our study we included 78 patients, in whom 49 (62.8%) masses were suggested to be benign, 24 (30.7%) malignant and 5 (6.4%) inconclusive according to IOTA simple rules. This was almost similar to Sharma B et al, [5] where according to usg IOTA rules 67.2% masses seemed benign and 26.2% as malignant. Timmerman D et al, [6] in their study found out the sensitivity and specificity of IOTA simple rules as 91% and 96% excluding inconclusive masses respectively and 94% and 80% taking inconclusive masses as malignant.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In our study we included 78 patients, in whom 49 (62.8%) masses were suggested to be benign, 24 (30.7%) malignant and 5 (6.4%) inconclusive according to IOTA simple rules. This was almost similar to Sharma B et al, [5] where according to usg IOTA rules 67.2% masses seemed benign and 26.2% as malignant. Timmerman D et al, [6] in their study found out the sensitivity and specificity of IOTA simple rules as 91% and 96% excluding inconclusive masses respectively and 94% and 80% taking inconclusive masses as malignant.…”
Section: Discussionsupporting
confidence: 89%
“…In a similar study by Sharma B et al, [5] the sensitivity of IOTA simple rules for the detection of malignancy was 92.8%, whereas the specificity was 93%, it had the positive predictive value of 81.2%, with a comparatively high negative predictive value of 97.5% and the accuracy of 92.9%. Our study showed positive predictive value of 87.5%, negative predictive value of 95.9% and accuracy of 93.2% excluding the inconclusive masses.…”
Section: Discussionmentioning
confidence: 78%